2017
DOI: 10.1021/acsami.7b07153
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Pressure Sensor Based on an Ultralight Sparkling Graphene Block

Abstract: Herein, we develop a supersensitive pressure sensor based on a fully air-bubbled ultralight graphene block through a simple sparkling strategy. The obtained sparkling graphene block (SGB) exhibits excellent elasticity even at 95% compressive strain and rebounds a steel ball with an ultrafast recovery speed (∼1085 mm s). Particularly, the SGB-based sensor reveals a record pressure sensitivity of 229.8 kPa, much higher than other graphene materials, because of the highly cavity-branched internal structure. Impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
99
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 57 publications
2
99
0
2
Order By: Relevance
“…Development in this area has been rapid with much effort having been focused on improving the sensitivity or durability of a single sensor . Exciting advancements have certainly been made in the field of flexible electronic devices in the last two decades and the sensing capabilities of tactile sensors have even exceeded those of human skins . At the same time, some studies have been made to mimic the human skin by implementing the multifunctional sensors through integration of several sensors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development in this area has been rapid with much effort having been focused on improving the sensitivity or durability of a single sensor . Exciting advancements have certainly been made in the field of flexible electronic devices in the last two decades and the sensing capabilities of tactile sensors have even exceeded those of human skins . At the same time, some studies have been made to mimic the human skin by implementing the multifunctional sensors through integration of several sensors .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Exciting advancements have certainly been made in the field of flexible electronic devices in the last two decades and the sensing capabilities of tactile sensors have even exceeded those of human skins. [3][4][5] At the same time, some studies have been made to mimic the human skin by implementing the multifunctional sensors through consists of a bottom interdigitated electrode and a top bridge of PANI-coated fabric. This type of multifunctional sensor has a high pressure sensitivity over a wide range of pressures (300 Pa-30 kPa) and an excellent linear response to NH 3 at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Uniform nanographene films obtained by chemical vapor deposition have been reported to exhibit a gauge factor of over 250, whereas the maximum strain was found to be less than 0.4% . To achieve force sensors with a high stress sensitivity and a large strain range, macroscopic 3D monoliths of these nanomaterials with high porosity and compressibility have been developed . Lv et al demonstrated a simple sparkling strategy to produce ultralight graphene blocks .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve force sensors with a high stress sensitivity and a large strain range, macroscopic 3D monoliths of these nanomaterials with high porosity and compressibility have been developed . Lv et al demonstrated a simple sparkling strategy to produce ultralight graphene blocks . Kim et al transformed an inelastic CNT aerogel into a superelastic material by coating it with graphene nanoplatelets .…”
Section: Introductionmentioning
confidence: 99%
“…A 1000‐fold times resistance change can be realized within a pressure range of 1–70 kPa. Totally, the fabricated multimeter‐like pressure sensor shows a wide pressure range from <1 Pa to 72 kPa with different ultrahigh sensitivities using different sensing parts (15.22 kPa −1 for 0–300 Pa, 0.22 kPa −1 for 0.09–30 kPa, and 46.67 kPa −1 for 48–72 kPa), which present the prominent advantages in both the sensitivity and pressure range than some previous reports (Table S1, Supporting Information) …”
mentioning
confidence: 99%